2019
DOI: 10.1146/annurev-immunol-042718-041812
|View full text |Cite
|
Sign up to set email alerts
|

Neuro–Immune Cell Units: A New Paradigm in Physiology

Abstract: The interplay between the immune and nervous systems has been acknowledged in the past, but only more recent studies have started to unravel the cellular and molecular players of such interactions. Mounting evidence indicates that environmental signals are sensed by discrete neuro–immune cell units (NICUs), which represent defined anatomical locations in which immune and neuronal cells colocalize and functionally interact to steer tissue physiology and protection. These units have now been described in multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
161
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(166 citation statements)
references
References 208 publications
(303 reference statements)
3
161
0
2
Order By: Relevance
“…In previous association studies, the metabolic pathway "PWY-5022 4-aminobutanoate degradation V", responsible for the breakdown of GABA into the SCFA butyrate, was identified as causally associated with increased insulin secretion following an oral glucose challenge (Sanna et al, 2019). Additionally, neuro-immunology is an emerging focus for disease pathogenesis, one that might be influenced by commensal metabolic pathways and bears further investigation (Godinho-Silva et al, 2019). Moving forward, as sample sizes increase, new microbe x immune interactions will continue to be uncovered.…”
Section: Clostridia Species Terrisporobacter Othiniensis Terrisporobmentioning
confidence: 99%
“…In previous association studies, the metabolic pathway "PWY-5022 4-aminobutanoate degradation V", responsible for the breakdown of GABA into the SCFA butyrate, was identified as causally associated with increased insulin secretion following an oral glucose challenge (Sanna et al, 2019). Additionally, neuro-immunology is an emerging focus for disease pathogenesis, one that might be influenced by commensal metabolic pathways and bears further investigation (Godinho-Silva et al, 2019). Moving forward, as sample sizes increase, new microbe x immune interactions will continue to be uncovered.…”
Section: Clostridia Species Terrisporobacter Othiniensis Terrisporobmentioning
confidence: 99%
“…Indeed, neuro-immune interactions have been intensively investigated in a number of settings, especially in the central nervous system (CNS) (Klein et al, 2017;Norris and Kipnis, 2019;Prinz and Priller, 2017). Moreover, 50 several recent studies have uncovered evidence for bidirectional communication between the peripheral nervous system (PNS) and the immune system in the spleen, bone marrow, intestine, airways, lungs and skin (Baral et al, 2019;Foster et al, 2017;Godinho-Silva et al, 2019;McMahon et al, 2015;Ordovas-Montanes et al, 2015;Veiga-Fernandes and Mucida, 2016). However, the mechanisms and consequences of these multi-facetted interactions are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Motor commands are relayed from the CNS to skeletal muscles and visceral organs, and executed by spinal motor 60 neurons and sympathetic/parasympathetic neurons, respectively. The autonomic motor neuron (i.e., sympathetic/parasympathetic neurons), have long been recognized for their impact on immunity (Chavan et al, 2017;Godinho-Silva et al, 2019), whereas the role of the somatosensory PNS as a critical immunomodulatory component has been appreciated only recently.…”
Section: Introductionmentioning
confidence: 99%
“…Although the immune and nervous systems clearly perform unique functions, they communicate and regulate each other to maintain homeostasis. Several studies have identified bidirectional crosstalk between nervous system and immune system in healthy state and pathologies in numerous conditions, including chronic inflammatory disorders, acute inflammatory conditions, autism, multiple sclerosis, and cancer (Louveau et al, 2015;Baral et al, 2018;Veiga-Fernandes and Mucida, 2016;Godinho-Silva et al, 2019). Recent studies have also revealed that specific anatomical locations of neuro-immune interactions may serve as important immunoregulatory hubs (Huang et al, 2019;Godinho-Silva et al, 2019;Veiga-Fernandes and Pachnis, 2017).…”
Section: Introductionmentioning
confidence: 99%